Surgical management of AN inverted AND impacted maxillary central incisor - case report - Nawaz, MKK (J West Afr Coll Surg, 2015)
Impacted maxillary permanent central incisor is not a frequently reported case in our dental practice. Dilaceration is one of the causes of failure of eruption of permanent maxillary incisor. It is a developmental anomaly of the form of a tooth that commonly occurs in permanent incisors .We report a case of a 14-year-old boy with an impacted central incisor in the maxillary region managed at Dr.H.Gordon Roberts’s hospital, Meghalaya, India. The tooth was completely upside down with the crown facing towards the nasal floor and the root towards the alveolar process with severe dilaceration. Surgical removal of the impacted central incisor was performed under local anesthesia without disturbing the floor of the nose.